2020
DOI: 10.1002/app.49883
|View full text |Cite
|
Sign up to set email alerts
|

Binary metal oxides incorporated polyethersulfone ultrafiltration mixed matrix membranes for the pretreatment of seawater desalination

Abstract: In this study, an attempt was made to pretreat seawater using polyethersulfone (PES) mixed matrix membranes (MMMs) incorporated with titania-based binary metal oxides. Two different titania-based binary metal oxides were prepared, namely titania-zirconia (TiZr) and titania-zinc oxide (TiZn). The influence of hydrophilic and negatively charged sulfonated poly(ether ether ketone) (SPEEK) polymer as additive of PES MMMs was also studied. Morphological and elemental analysis revealed that both ZrO 2 and ZnO were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…The functional group analysis of pristine, AEP, DDM, and AEP@DDM intermixed membranes was characterized by using FTIR analysis, and their spectra were illustrated in Figure 5. In SPES membranes, the peaks at 1151 and 1238 cm −1 corresponds to the sulfone group and aromatic ether band respectively and the peaks at 1485 and 1577 cm −1 were attributed to the C═C stretching 28 . Besides, with the sulfonation, the appearance of an absorption band at 1027 cm −1 represents the symmetric stretching vibration of sulfonate group 29 .…”
Section: Resultsmentioning
confidence: 99%
“…The functional group analysis of pristine, AEP, DDM, and AEP@DDM intermixed membranes was characterized by using FTIR analysis, and their spectra were illustrated in Figure 5. In SPES membranes, the peaks at 1151 and 1238 cm −1 corresponds to the sulfone group and aromatic ether band respectively and the peaks at 1485 and 1577 cm −1 were attributed to the C═C stretching 28 . Besides, with the sulfonation, the appearance of an absorption band at 1027 cm −1 represents the symmetric stretching vibration of sulfonate group 29 .…”
Section: Resultsmentioning
confidence: 99%
“…1b). 35 Except for TiO 2 , other metal oxides such as zinc oxide (ZnO) 36,37 and Zirconium dioxide (ZrO 2 ) 38 or metal sulfides such as cadmium sulfide (CdS) 39 were also employed as fillers for PES based MMMs in a similar way. However, despite the enhancement in antibacterial property, the water flux was usually decreased because of the pore plugging by nanoparticles especially under high mass loading.…”
Section: Pes Compositesmentioning
confidence: 99%
“…Furthermore, antibacterial tests revealed that PES/‐SPEEK/TiZr as well as PES/SPEEK/TiZn MMMs have superior biofouling resistance. For successful seawater pretreatment, SPEEK/PES MMM integrated hydrophilic binary metal oxide could be employed in combination UF‐RO as well as other salinity systems 145 …”
Section: Derivatives Of Speek Polymermentioning
confidence: 99%
“…This is because the SPEEK-ZrN nanohybrid membrane that has been constructed is a potential option for DMFC applications. 144 Lukka Thuyavan et al 145 produced TiO 2 ZrO 2 and TiO 2 ZnO based on hydrophilic titania, which they then put into a SPEEK/PES framework, resulting in better anticancer characteristics for seawater desalination. By increasing the loading of TiZr as well as TiZn, the hydrophilic characteristics including water resistance of the resultant membranes were also enhanced.…”
Section: Metal Oxides In Speekmentioning
confidence: 99%
See 1 more Smart Citation